339 Effect of varieties and tannin levels (low and normal) on the physicochemical and nutritional characterization of faba bean grown in western Canada. (7th December 2018) - Rodríguez, M; Guevara-Oquendo, V; Newkirk, R; Beaulieu, D; Tar'an, B; Yu, P
Abstract: The aim of this study was to evaluate the impact of varieties and tannin levels on physicochemical and nutritional characteristics of faba beans as alternative protein and energy source for ruminants. Eight varieties with 2 tannin levels (low vs. normal) grown in 3 locations in western Canada were analyzed. Chemical analyses were performed following the Association of Official Analytical Chemists (AOAC) standard methods, bioenergy values at maintenance and production levels were determined using NRC-2001. The experimental design was RCBD (varieties as fixed effect and locations as random block). MIXED model procedure of SAS 9.4 was used for statistical analyses with significance declared at P < 0.05. SAS contrast was used to compare low tannin and normal tannin varieties. Results showed there were no different in dry matter (DM), protein (CP), carbohydrates (CHO), and fiber content (NDF) with averages 93, 28, 68 and 18% DM, respectively. Ash, starch, and non-structural carbohydrates (NSC) were higher (P < 0.05) in low tannin varieties (LT) while organic matter (OM) and lignin were greater (P < 0.05) in normal tannin varieties (NT). Soluble crude protein (SCP) was highly significant different (P < 0.01) in LT compared to NT (21% vs. 18%). The rapidly degradable protein fraction (PA2) showed high significant difference (P < 0.01) in LT compared to NT (74% vs. 62%) while the later showed a higher mean (P < 0.01) on slowly degradable protein fraction (PB2) compared to LT (8% vs. 5%); the mean value of intermediately degradable protein fraction (CB1) was significantly higher (P < 0.05) on LT. No significant difference (P>0.10) was observed on total digestible nutrients (TDN1x), metabolizable protein (MP), rumen degraded protein balance (DPB), and feed milk value (FMV). Even when results showed difference on physicochemical characteristics among seeds, the predicted animal performance and production was not different. These outcomes suggest that faba beans can be use as nutritive ingredient for ruminant diets without a significant tannin level effect.